ANCIENT MEASURES IN FICTION - Alaudinova Rukhsora Ramazon Kizi (Scholar Express Journal, 2021)
Not all the words that I met in the texts were familiar. Most of them are old measurements of length, weight, volume. As it turned out later, understanding these measures causes difficulties for many children. We hardly use them in modern language. Only when reading works of art do we come across these concepts. But, nevertheless, we must know the values of the measures. This is our story. I was interested in this topic, and I decided to seriously engage in the study of units of measurement of length, weight, volume, as well as monetary units, based on the works of different genres. After all, it is not for nothing that the Russian proverb says: "You can't weave a bast shoe without measure."
Keywords: factor, root, reputation, case, determinant